Nahwu Analysis Activities in Reading the Text of Natsar Al-Barzanji and Its Effect on The Ability of Reading Arabic Texts - Rina Septiani; Riska Hermina Rahmawati; Risna Nurul Insani (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2023)
Purpose: This study, conducted at Al-Mardhiyyah Al-Islamiyyah Islamic Boarding School, investigates the impact of incorporating nahwu (Arabic syntax) analysis into the traditional reading of Natsar al-Barzanji on students' Arabic reading abilities. Originally part of the